Project-Based Learning Based on Papuan Local Wisdom: Its Impact on Collaboration Ability and Understanding of the Concept of Two-Dimensional Shapes - Via Luftiatun Nabila; Oki Sandra Agnesa; Sella Nofriska Sudrimo (MASI Mandiri Edukasi, 2026)
The low level of students' collaboration skills and conceptual understanding in mathematics, particularly on 2D shapes, requires an innovative learning approach. This study aims to determine the effectiveness of Project-Based Learning (PjBL) based on Papuan local wisdom in improving collaboration skills and understanding of 2D shapes among fifth-grade students of MI Al-Ma'arif Sorong City. This research employed a quantitative approach using a quasi-experimental design with a Nonrandomized Control-Group Pretest–Posttest design. The subjects consisted of an experimental class and a control class. Data were collected through written tests, observation sheets, and documentation. The data were analyzed using N-Gain calculation, Mann–Whitney U test, and Independent Sample t-Test to determine significant differences between the two groups. The results showed that the implementation of PjBL based on Papuan local wisdom significantly improved students’ collaboration skills and conceptual understanding. The experimental class achieved a medium category improvement, while the control class remained in the low category. These findings indicate that integrating Papuan local wisdom into the PjBL model is effective in enhancing students’ social skills and deeper mathematical concept mastery.